Performing Asian America : race and ethnicity on the contemporary stage - Lee, Josephine, 1960- (Asian American history and culture., 1997)
In her groundbreaking book, Performing Asian America, Josephine Lee meets a formidable challenge. How does one go about describing and analyzing the cultural production of Asian Americans, a group just beginning to make their complex political and social positions more visible? Lee approaches her specific subject, how Asian American playwrights depict race and ethnicity onstage, from the perspective that theatrical performances and dramatic texts can tell us much about these contemporary dynamics.